Across the Unseen Sea and Dinner for Deep Surface Divers - Stehlíková, Tereza (InTensions, 2018)
Dinner for Deep Surface Divers uses food as a poetic medium, where eating is depicted as a highly sensual act, while exploring the role of the senses and embodiment in informing our vision. Across the Unseen Sea captures the essence of a multi-sensory banquet that I created and which took place in London, in 2013. I based the event on William Morris’s diary entries from his journey to Iceland, in 1871/73 and “translated” these into a multi-sensory immersive performance. The project was developed in collaboration with Charles Michel (cook and researcher at Charles Spence’s Crossmodal Research laboratory, Oxford), as well as a team of dedicated collaborators from various backgrounds and with different professional expertise (set, sound, scent designers, actors, food historians etc.). The film was created with the intention of communicating the subjective, multi-sensory experience of one of the guests, a writer, by audio-visual.